Iron-Modified Composite Adsorbent Coating For Acid Red 1 Removal And Its Regeneration Feasibility By Heterogeneous Fenton-Like Process - Chew, Jian Yee (Universiti Sains Malaysia, 2018)
Adsorption is widely used technique in wastewater treatment because the process is low cost, ease of operation and efficient. However, regeneration of spent adsorbents is usually restricted by the strong interactions between the surface of adsorbents and adsorbates. It would be very economical if the spent adsorbents can be regenerated and reused for many cycles. Hence, this current research had been focussed on the feasibility of heterogeneous Fenton process to regenerate Acid Red 1 (AR1) loaded composite adsorbent coating (CAC). The iron-modified bentonite was synthesised to replace swelled bentonite in the original formulation of CAC (APE-bent-EPIDMA/CF). The results showed that the adsorption of AR1 with initial concentration of 50 ppm was very efficient and equilibrium was achieved within two hour for both formulations. After modified with iron, the removal rate of AR1 in aqueous solution was higher than that of swelled bentonite. Ability of heterogeneous Fenton process to regenerate the spent APE-Febent-EPIDMA/CF was evaluated under the assistance of UV and without UV (in dark condition). The effect of acid and base on the desorption of AR1 was also studied using 0.1 M of hydrochloric acid (HCl) and 0.1 M sodium hydroxide (NaOH). The initial concentration of hydrogen peroxide used was 8.82 mM. After regeneration process for 3 hours under the UV assistance with addition of 0.1 M NaOH, the APE-Febent-EPIDMA/CF was still able to retain high percentage removal of AR1 (>80%) up to five cycles of adsorption. The findings revealed that sodium hydroxide is a good elution agent to desorb AR1 (anionic dye) from the APE-Febent-EPIDMA/CF coating.